New Attorney Bar Admission Ceremony at Valdez Hall Wine Room - Watkins, Howard::::::::: (1987)
Fresno County Bar Association President Herbert Levy welcoming all of the new admittees Fifth Appellate District Justices in background: Judge Blaine Pettitt; Justices Robert Martin, ? , Donald Franson, Charles Hamlin, George Zenovich, ?and Federal District Court Judge M.D. Crocker